(untitled) (Journal of the College of Basic Education, 2022)
Any discourse must have a material for it, consisting of content or content, and this discourse must have methods that make this production have an aesthetic feature that highlights that content, and then clarify the purpose or significance of it. The material of literature is life in all its details. Ourselves from experiences and scenes, there must be an image that stems from all of this, and this image we call rhetorical methods, as these images suggest many revelations, affecting the speech producer and recipient with various effects, until they are deposited in the minds and imprinted in them (1).